Case Report: The ectopic pancreas in the adrenal glands: It was found due to elevated blood pressure and initially diagnosed as adrenal adenoma - Zhang, Tao; Yin, Si-fan; Wang, Qi-wu; Feng, Wen-bo; Ke, Chang-xing (Frontiers in Surgery, 2022)
The ectopic pancreas is a kind of congenital malformation formed during embryonic development, which has no anatomical relationship with the normal pancreas and is a rare solid disease. The ectopic pancreas in the adrenal glands is extremely rare.